Metabolic pathway of Cis-UCA upon Ultraviolet B (UVB) exposure using ¹H Nuclear Magnetic Resonance (NMR) spectroscopy, Molecular Docking and cell viability of human keratinocytes (HaCaT) cell lines - Ali Musa, Aina Yusrina (2026)
Urocanic acid (UCA), a histidine metabolite, is found in the stratum corneum protects and modulates the immune system. Metabolism of photoisomerization trans-XJCA to cis-UCA is unknown. In 2001, Kinuta et al. (2001) proposed cis-UCA metabolism pathway but did not clarify the conversion of glutathione conjugates, GS(CIE) to cysteine conjugates, Cys (CIE), leaving a critical mechanistic gap. The primary goal of this study was to investigate the cis-UCA metabolic pathway via conjugation with sulphide-derivative chemicals to resolve this unknown phase. Briefly, Nuclear Magnetic Resonance (NMR) metabolomic approach was used to study the reaction of cis-UCA with various sulphide donors including N-acetylcysteine (NAC), glutathione (GSH), L-cysteine, sodium hydrosulphide (NaHS) and sodium disulphide (Na2S2) in a cell-free system. Next, a molecular docking analysis was performed to evaluate the interaction of glutathione-S-transferase (GST) with glutathione conjugate, followed by bioassay analysis using Human Keratinocyte Cells (HaCaT). From the results, it was found that cis-UCA can readily react with the reactive sulphur species (RSS) donors with no involvement of GST enzyme. A new compound named 4-imidazoleacrylic acid-3-thiol was discovered when the cis-UCA reacted with NaHS. Furthermore, although the original pathway reported that the formation of these GS(CIE) and Cys (CIE) is catalysed by GST, results show that both compounds can form even without GST, indicating that the reaction can occur non-enzymatically. Next, through molecular docking experiments, the GS(CIE) shows a greater binding affinity with GST than the reference drug sulforaphane, implying a potential regulatory role of GS(CIE) towards the physiological function of GST. The in vitro studies showed that UVB exposure together with cis-UCA significantly reduced cell viability, although the presence of sulphide donors appeared to alleviate toxicity. This study gives new insight into the cis-UCA metabolism and perhaps sheds light on the potential role of UCA in general as a photo transmitter compound. Overall, this study illustrates that cis-UCA engages in non-enzymatic conjugation with RSS, resulting in the formation of novel metabolites, 4-imidazoleacrylic acid-3-thiol. Significantly, RSS co-treatment inhibited cis-UCAenhanced UVB cytotoxicity, confirming a protective role of sulphide donors. These results modify the old GST-dependent model and endorse an alternate RSS-driven pathway in cis-UCA metabolism, with effects for UCA's role in UVB-induced skin reactions.